Desain Sistem Informasi Entry Biodata Mahasiswa Siswa Baru Universitas Prima Nusantara - Muhammad Ridho; Sarjono Sarjono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the era of digitalization at universities, one of which is Prima Nusantara University, managing student data has become an important aspect for higher education institutions to support campus administration activities. This research aims to design a student biodata entry information system that is efficient, integrated and easy to access. This system is designed to automate the registration process and manage student data, which was previously done manually or Google from in collecting student biodata, thereby reducing the risk of errors and duplication of data. A prototype student biodata entry information system that allows users to input, update and manage student data. real-time integrated at Prima Nusantara University, especially for new student data, for campus administration purposes, data is usually collected manually, so I am interested in creating an information system for new student data entry in searching for student data on the Prima University campus. Archipelago